Handbook of Florida Water Regulation: Florida Springs and Aquifer Protection Act - Tatiana Borisova; Michael T. Olexa; Jarrett Davis (EDIS)
This handbook is designed to provide an accurate, current, and authoritative summary of the principal federal and state laws that directly or indirectly relate to agriculture. Written by Tatiana Borisova, Michael T. Olexa, and Jarrett Davis and published by the UF/IFAS Food and Resource Economics Department, this chapter of the handbook provides a basic overview of the Florida Springs and Aquifer Protection Act. http://edis.ifas.ufl.edu/fe1019